2016
DOI: 10.1038/ncomms13418
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific roles of the cytoplasmic polyadenylation factor CPEB4 in the regulation of melanoma drivers

Abstract: Nuclear 3'-end-polyadenylation is essential for the transport, stability and translation of virtually all eukaryotic mRNAs. Poly(A) tail extension can also occur in the cytoplasm, but the transcripts involved are incompletely understood, particularly in cancer. Here we identify a lineage-specific requirement of the cytoplasmic polyadenylation binding protein 4 (CPEB4) in malignant melanoma. CPEB4 is upregulated early in melanoma progression, as defined by computational and histological analyses. Melanoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 69 publications
1
47
0
Order By: Relevance
“…In addition to transcriptional regulation, as might be expected for a key transcription factor, MITF is also subject to posttranscriptional regulation via both control of its mRNA polyadenylation by CPEB4 (Pérez-Guijarro et al 2016) and the action of microRNAs that play a key role in melanoma biology (Bell and Levy 2011;Kunz 2013). To date, several microRNAs have been described as inhibiting MITF expression, including miR-26a in melanoma (Qian et al 2017), miR-340 in osteoclasts (Zhao et al 2017), and miR-137 (Bemis et al 2008), miR-148 (Haflidadóttir et al 2010, miR-155 (Arts et al 2015), and miR-182 (Yan et al 2012).…”
Section: Repressors Of Mitf Mrna Expressionmentioning
confidence: 99%
“…In addition to transcriptional regulation, as might be expected for a key transcription factor, MITF is also subject to posttranscriptional regulation via both control of its mRNA polyadenylation by CPEB4 (Pérez-Guijarro et al 2016) and the action of microRNAs that play a key role in melanoma biology (Bell and Levy 2011;Kunz 2013). To date, several microRNAs have been described as inhibiting MITF expression, including miR-26a in melanoma (Qian et al 2017), miR-340 in osteoclasts (Zhao et al 2017), and miR-137 (Bemis et al 2008), miR-148 (Haflidadóttir et al 2010, miR-155 (Arts et al 2015), and miR-182 (Yan et al 2012).…”
Section: Repressors Of Mitf Mrna Expressionmentioning
confidence: 99%
“…Therefore, it will be interesting to address to which extent this melanoma RBP landscape is shared with other tumor types. In particular, genes modulating 3′ UTR-associated functions may provide insight into the control of lineage specification as we recently reported for the cytoplasmic polyadenylation factor CPEB4 20 . In this context, unbiased transcriptomic and proteomic data sets generated here may serve as a tractable platform for the identification of new roles of RBPs controlling the still elusive mechanisms underlying lineage specificity or tumor-type identity.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, X-ray 43 and nuclear magnetic resonance studies 44 revealed that CELF1 is organized in complex 3D oligomeric structures with open and close conformations that could result in ambiguous readings of iCLIP. Therefore, we selected to perform RNA immunoprecipitations (RIP) using protocols we have proven efficient for RBPs such as the cytoplasmic polyadenylation factor CPEB4 in melanoma cells 20 . RIP was then followed by RNA sequencing (RIP-Seq), resulting in at least 10 million reads/sample aligned to the human genome (GRCh37/hg19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations